Pengaruh Metode Guided Discovery Inquiry Dan Berpikir Kreatif Terhadap Keterampilan Menulis Cerpen Pada Siswa Kelas X SMA - Melyawati Melyawati (Universitas Mathla'ul Anwar Banten, 2017)
This research was done at the X-1 and X-2 grade of SMAN 10 Pandeglang by using experimental methods to design Experiment by Treatment two factorial design. The quantitative data was gathered by written an creative thinking test. The data analysis used ANOVA 2 way and it was analized by using SPSS 16 programe. The results of data was shown that: (1) there are significant differences short story witting skill between Guided Discovery-Inquiry and expository method; (2) there are significant of story writing skill difference between students who have high creative thinking and those who have low creative thinking; (3) the are interaction of Guided Discovery-Inquiry method and creative thinking snd its influence toward students short story writting skill; (4) there are difference between students’ short story writing skills who used Guided Discovery-Inquiry and those who used expository learnig method; (5) there are differences between student’s short story writing skill who used low Guided Discovery-Inquiry and those who used low axpository learning methods.